Synthesis, antitumor activity evaluation of some new N-aroyl-α, β-unsaturated piperidones with fluorescence. (3rd May 2016) - Sun, Jufeng; Wang, Suwen; Li, Hongjuan; Jiang, Wenguo; Hou, Guige; Zhao, Feng; Cong, Wei
Abstract: Novel N -aroyl-α, β-unsaturated piperidones, series1, series2 and series3 (featuring 2-bromo-4, 5-dimethoxybenzylidene, 4-dimethylaminobenzylidene and 4-trifluoromethylbenzylidene, respectively), were synthesized as candidate cytotoxins. Most of the compounds displayed potent cytotoxicity against the human neoplastic cell lines SK-BR-3, PG-BE1, NCI-H460, MIA PaCa-2 and SW1990 in vitro, and approximately 64% of the IC50 values were lower than 5 μM. Among those tested, compound1b of series1, 3a, 3d and3e of series3 proved to be the most active. Importantly, 1b displayed marked inhibitory effects on tumor growth in vivo and had no apparent toxicity to mice; this was evaluated by a nude mouse PG-BE1 xenograft model. In addition, the fluorescent properties of compounds series1 –3 were investigated. The interesting fluorescence exhibited by these compounds could be useful for their visualization in tumor cells, permitting further studies on these α, β-unsaturated piperidones as candidates for novel fluorescent antitumor agents.